The Handbook of English pronunciation - Reed, Marnie; Levis, John (John M.) (Blackwell handbooks in linguistics, 2015)
"The Handbook of English Pronunciation presents a comprehensive exploration of the characteristics of English pronunciation, including language acquisition, English in the world, its relationship to modern technology, the shifting role of accent, and more"--Provided by publisher.